Ein Bestseller der islamischen Vormoderne Zur Verbreitung von Ḫvāndamīrs Ḥabīb as-siyar von Anatolien bis auf den indischen Subkontinent - Bockholt, Philip (Veröffentlichungen zur Iranistik; PHILOSOPHISCH-HISTORISCHE KLASSE SITZUNGSBERICHTE, 2022)
The Persian world history "Ḥabīb al-siyar" is one of the most copied historiographical works in Islamic intellectual history. Written by the Iranian historian Khvāndamīr in Herat during the rule of the Shiʿi Safavids in the 1520s, the book was subsequently adapted to the religious and political expectations of his later patrons, the Sunni Mughals in India, and circulated through hundreds of copies spread across the entire eastern Islamic world. In "Ein Bestseller der islamischen Vormoderne" ("An Early Modern Bestseller"), Philip Bockholt analyses copies of the work and offers new insights into their readership at various locations in the premodern Islamic world. Taking cues from reception, provenance, and historical readership studies, he examines ownership and readership notes, endowment seals and illustrations in order to shed light on the owners and readers of the work between the 16th and early 20th centuries. By giving an in-depth analysis of marginal notes found in the extant copies, he situates the "Ḥabīb al-siyar" within the broader framework of Islamic book culture and shows that the chronicle was part of a larger canon of texts. This canon was read within a greater Persianate world including not only the Safavid court in Iran and the Mughal court in India, but also places on the Deccan as well as in Central Asia and the Ottoman Empire. This study thus offers comprehensive insights into the transregional transmission of Persian historiography as well as regionally specific readership practices.